Natural history of Ctenus medius Keyserling, 1891 (Aranae, Ctenidae) II: life cycle and aspects of reproductive behavior under laboratory conditions - FOLLY-RAMOS,E. (2002)
Ctenus medius Keyserling, 1891 is a wandering spider common in the Brazilian Atlantic Forest. It has been the subject of few studies. Thus, this work aims to elucidate aspects of its natural history, such as the life cycle and reproductive behavior of this species, through laboratory and field observations. Two females with egg sacs were observed in the laboratory and one was observed in field (Barra Mansa, 22º32'S and 44º10'W) until the emergence of the spiderlings. For observation of the immature stage development, a portion of the spiderlings from the same hatch were taken to the laboratory and watched until sexual maturity. In the field, the period between the oviposition and the emergence of spiderlings was of 36 days. The female selects a site for egg sac deposition and stays there until the spiderlings emerge. Seven days after the emergence, the female abandoned the site where the egg sac was made, concomitant to the spiderlings dispersion from observation's place and until the moment that the spiderlings started to eat. For the spiderlings kept under laboratory conditions, cannibalism was not observed in the first instars (1-4th) when sufficient food was offered. Sexual maturity happened in the 14th or 15th instars, with an average of 309.2 to 344.5 days until the last/sexual molt, respectively. Until the date of sexual maturity, there was a mortality rate of 85%. This species is very fragile in captivity. This hampered deductions concerning longevity. Both females and males collected in the field were induced to mate in the laboratory. Courtship movements of males were registered, but the females did not permit the mating. These data may assist in initial biological studies of Ctenus genus and offer comparative parameters for studies of other related species.